1997
DOI: 10.1093/treephys/17.11.741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crop load on fruiting and leaf photosynthesis of 'Braeburn'/M.26 apple trees

Abstract: Four-year-old apple (Malus x domestica Borkh.) trees cv. 'Braeburn' on M.26 rootstock were thinned at full bloom to establish six crop loads ranging from a heavy crop to a deflowered treatment. At harvest, mean yield per tree varied from 0 to 38 kg and mean fruit weight ranged from 225 g in the heaviest cropping treatment to 385 g in the lightest cropping treatment. Light cropping resulted in a significant advance in fruit maturity as indicated by background color, starch/iodine score and soluble solids. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
75
2
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 10 publications
13
75
2
4
Order By: Relevance
“…Short-term rates of photosynthesis of the 'Royal Gala' leaves during the treatments, typically c. 6 |Amol m-2 s-1 , were relatively low compared to other measured rates of photosynthesis in apple leaves (Flore & Lakso 1989;Wünsche et al 1996;Palmer et al 1997). However, the rates measured in the present study compared favourably with rates for apple trees without crop or taken a considerable time after harvest (cf.…”
Section: Discussioncontrasting
confidence: 53%
“…Short-term rates of photosynthesis of the 'Royal Gala' leaves during the treatments, typically c. 6 |Amol m-2 s-1 , were relatively low compared to other measured rates of photosynthesis in apple leaves (Flore & Lakso 1989;Wünsche et al 1996;Palmer et al 1997). However, the rates measured in the present study compared favourably with rates for apple trees without crop or taken a considerable time after harvest (cf.…”
Section: Discussioncontrasting
confidence: 53%
“…Similar findings were documented for coffee in (Vaast et al 2005;Vaast et al 2006) and other fruit tree species, e.g. apple (Palmer et al 1997) and peach (Corelli-Grappadelli and Coston 1991). The current study also revealed smaller relative variability the larger the mean bean dry weight (Figs.…”
Section: Weight and Size Of Beanssupporting
confidence: 78%
“…The source was little affected by the pruning treatments, therefore an improved fruit: leaf relationship cannot explain the larger fruit. Palmer et al (1997) reported that leaf assimilation is stimulated by crop productivity (increase in sink size) and that the leaf assimilation rate is curvilinear with crop load for 'Braeburn' apples, up to a maximum crop of 12 fruit m -2 leaf area. In non-bearing trees the leaf assimilation rate was at times 64 percent lower rate than that of heavy cropping trees.…”
Section: Fruit Sizementioning
confidence: 99%